Cyclic Production of Flexible Manufacturing Cells - Nejad, Mazyar Ghadiri (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
This thesis deals with two different flexible manufacturing cells. Both cells contain m identical computer numerical control (CNC) machines that are able to perform all the processes to produce a final product. The CNC machines are set up in a line layout. In the both cases, one input station and one output station exists at the beginning and at the end of the line, respectively. The items to be processed are kept in the input station, and the finished items are kept in the output station. In the second case, in addition to the input station, there is an individual input buffers attached to each machine. Using these buffers, each machine can be consecutively loaded twice in a cycle. In the both cells, a robot serves the machines and transports parts from the input station to a machine, loads the machine, and unloads the machine, after finishing its process, and puts the processed part in the output station. In these cells, m different parts will be processed in every cycle. Each part is processed completely by one machine. If the system is at a specific state at the beginning of a cycle, it reaches the same state at the end of the cycle, and then repeats the same actions in the same order in the subsequent cycles. To show all of the possible cycles in such cells, a sequential part production matrix is presented considering a general case. The duration of a cycle is called cycle time. The objective function of both cell types is to find the order of robot operations that minimizes the cycle time which maximizes the long-run average throughput rate of each cell. For the first case, a new mathematical model is presented to optimize the system. A reduced version of the new model is also provided. The reduced version is still an exact model of the minimization of the cycle time, however it does not determine the waiting times of the robot directly. These two models are more effective than the previous existed exact models in the literature. The solution of the reduced model requires significantly less CPU time comparing to the other models. A metaheuristic algorithm based on simulated annealing algorithm is proposed. In order to compute the minimum cycle time in each iteration of the algorithm, a linear programming model is needed to be solved which is the first case in the literature to the best of our knowledge. A new proof is provided for the lower bound of cycle time. This new proof facilitates the optimality analysis of several sequences of the robot movements. For the second case, a mathematical model is presented to optimize the cyclic production. A two-machine cell is discussed in details. In addition to some lower bounds of the cycle time for different orders of robot movements, the optimal cycles and upper bounds for the cases with different activities are also investigated.

ÖZ: Bu tez iki farklı esnek imalat hücresi ile ilgilidir. Her iki hücre de, nihai bir ürün üretmek için tüm işlemleri gerçekleştirebilen, aynı sayıda Bilgisayarlı Sayısal Dentim (CNC) makinesini içerir. CNC makineleri bir çizgi düzeninde ayarlanır. Her iki durumda da sıranın başında ve sonunda bir giriş istasyonu ve bir çıkış istasyonu bulunur. İşlenecek parçalar giriş istasyonunda tutulur ve bitmiş parçalar çıkış istasyonunda tutulur. İkinci durumda, giriş istasyonuna ek olarak, her bir makineye bağlı tek bir giriş tamponları bulunur. Bu tamponları kullanarak, her makine ardışık olarak bir döngüde iki kez yüklenebilir. Her iki hücrede de, robot makinelere hizmet eder ve parçaları giriş istasyonundan makineye nakleder, makineyi yükler ve işlemi tamamladıktan sonra makineyi boşaltır ve işlenmiş kısmı çıkış istasyonuna koyar. Bu hücrelerde, her döngüde m sayıda farklı parça işlenecektir. Her parça bir makina tarafından tamamen işlenir. Sistem bir çevrimin başlangıcında belirli bir konumdaysa, çevrimin sonunda da aynı duruma geçer ve aynı aktiviteleri sonraki çevrimlerde de aynı sırada tekrarlar. Bu tür hücrelerdeki olası döngülerin tümünü de göstermek için, genel durum göz önüne aknarak ardışık parça üretim matrisi sunulmaktadır. Bir döngünün süresi döngü süresi olarak adlandırılır. Her iki hücre tipinin amaç fonksiyonu, her bir hücrenin uzun dönem ortalama çıktı oranını maksimize eden döngü süresini en aza indirecek robot işlemlerinin sırasını bulmaktır. İlk durumda, sistemi optimize etmek için yeni bir matematiksel model sunulmuştur. Yeni modelin indirgenmiş bir versiyonu da gösterilmiştir. İndirgenmiş versiyon, döngü süresinin en aza indirgenmesinin hala kesin bir modeli olmasına rağmen robotun bekleme sürelerini doğrudan belirlememektedir. Bu iki model literatürde daha önce var olan kesin modellere göre daha etkilidir. İndirgenmiş modelin çözümü, diğer modellere kıyasla çok daha az CPU zamanı gerektirir. Benzetimli tavlama algoritmasına dayanan sezgi ötesi bir algoritma önerilmiştir. Algoritmanın her yinelenmesinde minimum döngü süresini hesaplamak için doğrusal bir programlama modelinin çözülmesi gerekmektedir. Döngü süresinin alt sınırı için yeni bir ispat gösterilmiştir. Bu yeni ispat, robot hareketlerinin birkaç sırasının optimallik analizini kolaylaştırımaktadır. İkinci durumda, döngüsel üretimi optimize etmek için bir matematiksel model sunulmuştur. İki makine hücresi ayrıntılı olarak ele alınmıştır. Robot hareketlerinin farklı sıraları için döngü zamanının bazı alt sınırlarına ilaveten, farklı aktivitelere sahip durumlar için optimal çevrimler ve üst sınırlar da araştırılmıştır.
Doctor of Philosophy in Industrial Engineering. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2018. Supervisor: Prof. Dr. Bela Vizvari.
Keywords: Industrial Engineering; Production Management; Flexible manufacturing; CNC machines; Robotic cell; Cyclic scheduling.; Metaheuristics